Next Generation GNSS Single Receiver Cycle Slip Reliability - Teunissen, Peter; de Bakker, Peter (Springer, 2012)
In this contribution we study the multi-frequency, carrier-phase slip detection capabilities of a single receiver. Our analysis is based on an analytical expression that we present for the multi-frequency minimal detectable carrier phase cycle slip.